Transformation leadership with knowledge sharing and employee career growth: the role of self-efficacy and psychological capital - Bai, Yun (Frontiers in Psychology, 2025)
Existing research lacks a systematic exploration of the relationships among transformational leadership, knowledge sharing, and employee career growth, as well as the mechanisms of self-efficacy and psychological capital in this context, especially the integrated analysis of mediating and moderating effects. This study aims to fill this gap by constructing a structural equation model based on social exchange theory and comprehensively applying qualitative and quantitative research methods. It deeply analyzes how transformational leadership promotes employee career growth through knowledge sharing and reveals the moderating and strengthening roles of self-efficacy and psychological capital. Based on 412 valid questionnaires and 15 in—depth interview data, methods such as descriptive statistics, regression analysis, mediating effect test, and moderating effect test were used to systematically verify the internal relationships among variables, providing new theoretical perspectives and empirical support for organizational management practices. The study found that transformational leadership has a significant positive impact on employee career growth (β = 0.603, p < 0.001), and knowledge sharing plays a partial mediating role between them (mediating effect value = 0.1505); self-efficacy significantly moderates the relationship between transformational leadership and knowledge sharing (β = 0.412, p < 0.001), and the mediating effect of knowledge sharing gradually weakens as the level of self-efficacy increases (low level: 0.0994; high level: 0.0615); psychological capital strengthens the positive relationship between transformational leadership and knowledge sharing (β = 0.422, p < 0.001) and enhances the mediating effect of knowledge sharing (low level: 0.1094; high level: 0.0715). Theoretically, this study enriches transformational leadership theory, deepens the understanding of the mediating mechanism of knowledge sharing, and expands the application boundaries of self-efficacy and psychological capital in organizational behavior. Practically, it suggests that enterprise managers should pay attention to cultivating transformational leadership styles, especially by improving leadership effectiveness through the four dimensions of moral example, visionary motivation, individualized consideration, and leadership charisma.